2019
DOI: 10.12659/msm.915034
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Complex Renal Calculi by Digital Flexible Ureterorenoscopy Combined with Single-Tract Super-Mini Percutaneous Nephrolithotomy in Prone Position: A Retrospective Cohort Study

Abstract: Background Advances in percutaneous nephrolithotomy (PCNL) have resulted in smaller devices that cause less trauma and bleeding, while flexible ureterorenoscopy (f-URS) allows access to any calyces. These methods are often used in isolation, but used in combination they may improve treatment of complex renal calculi. This study assessed the effectiveness and complications of f-URS combined with super-mini-PCNL (SMP) to treat complex renal calculi. Material/Methods A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 34 publications
3
23
1
Order By: Relevance
“…Although the postoperative complication rate was higher in the combined group, these complications were minor as seen in the previous studies [15]. Besides, the patients with a stone size of more than 5cm had the most complications.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Although the postoperative complication rate was higher in the combined group, these complications were minor as seen in the previous studies [15]. Besides, the patients with a stone size of more than 5cm had the most complications.…”
Section: Discussionsupporting
confidence: 51%
“…The total operative time in the combined group was reasonable as in RIRS and PCNL groups. Several factors have been stated in the literature on the impact of operative time during urological surgery [15,19,20]. One factor that increased the operative time might be time for blood transfusion [19], which was the case in the combined group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic combined intrarenal surgery (ECIRS) is a new technique that can perform PNL and FURS simultaneously, also can reduce the number of access tracts [ 13 ]. Related studies have confirmed that the use of single tract minimally invasive ECIRS (stmECIRS) for staghorn calculi has a high SFR and few postoperative complications [ 14 16 ]. ECIRS commonly uses the Galdakao-modified supine Valdivia (GMSV) position and the prone split-leg position [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the GMSV position has some disadvantages, including the collapse of the pyelocaliceal system, difficulties of renal puncture, and smaller space for instrument manipulation, especially in obese patients [ 19 ]. Urologists are more familiar with the prone position, but in the prone split-leg position, the learning curve is relatively high to find the ureteral orifice and place the flexible ureteroscope sheath by using FURS in the prone position, particularly in men with ureteral stricture [ 16 , 20 ], and the actual operation space of the perineal area is small.…”
Section: Introductionmentioning
confidence: 99%